Ludwig Wittgenstein: Remarks on the foundations of mathematics. Part IV 1942-1944 - Wittgenstein, Ludwig; Monsalve-Solórzano, Alfonso (Estudios de Filosofía, 1990)
"The axioms of an axiomatic system must be self-evident." How, then, are they self-evident? What if I said: this is how I find it easiest to imagine. And here imagining is not a particular mental process in which one closes his eyes or covers them with his hands.